Bank resolutions through M&As: The case of Ghana's purchase and assumption agreement - Fan Yang; Nana Adwoa Anokye Effah (Cogent Business & Management, 2023)
In this article, we examine the possible effects of acquisition through a Purchase and assumption agreement (P&A) as a resolution approach by the central bank of Ghana on the performance of the acquiring bank post-acquisition. By assessing the execution of the first P&A agreement, we contribute to the dearth of literature on the impact of M&As on bank performance in a developing context. We use secondary data from the Ghana Stock Exchange and the acquirer's financial reports from 2015 to 2019 to assess the likely performance changes. We employ event study methodology and ratio analysis to determine the impact. We observe that while depositor funds were saved and the acquirer succeeded in widening their asset base through the acquisition, their efficiency levels during the assessed period did not improve. Our findings help explain the effects of such M&As through P&As on bank performance to assist investors and management in decision-making. It further accentuates the importance of adequate preparations before embarking on any sort of P&A agreement.
Keywords: 650; accounting ratios; banking industry; event study; Mergers and Acquisitions (M&As); purchase and assumption agreement